2013
DOI: 10.1128/aem.02290-12
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella Transcriptome in Lettuce and Cilantro Soft Rot Reveals a Niche Overlap with the Animal Host Intestine

Abstract: bFresh vegetables have been recurrently associated with salmonellosis outbreaks, and Salmonella contamination of retail produce has been correlated positively with the presence of soft rot disease. We observed that population sizes of Salmonella enterica serovar Typhimurium SL1344 increased 56-fold when inoculated alone onto cilantro leaves, versus 2,884-fold when coinoculated with Dickeya dadantii, a prevalent pathogen that macerates plant tissue. A similar trend in S. enterica populations was observed for so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 78 publications
4
99
0
Order By: Relevance
“…It involves major changes in the bacterial transcriptome and requires genes involved in amino acid biosynthesis and transport, cellulose production, fimbriae, regulators, and surface structures (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Some of the same mechanisms were involved in the colonization of both vegetative and reproductive tissues on different plant species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It involves major changes in the bacterial transcriptome and requires genes involved in amino acid biosynthesis and transport, cellulose production, fimbriae, regulators, and surface structures (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Some of the same mechanisms were involved in the colonization of both vegetative and reproductive tissues on different plant species.…”
mentioning
confidence: 99%
“…The capacity of S. enterica (and other enteric pathogens) to readily multiply within plant tissues led to the hypothesis that persistence on plants is a part of the Salmonella life cycle, serving as reservoirs prior to reinfection of the preferred animal hosts (2)(3)(4)(5). Several studies have dissected the molecular basis of plant-Salmonella interactions (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, the entire complement of genetic functions required for plant colonization by Salmonella is not yet known.…”
mentioning
confidence: 99%
“…Interestingly, propanediol is a metabolite resulting from ripening or rotting of plant tissues (Bobik et al, 1997;Brandl et al, 2013;Goudeau et al, 2013). Previous studies revealed that populations of mutants deficient in propanediol utilization were several logs lower than wild-type strains grown in cilantro (Goudeau et al, 2013). In the light of S. Saintpaul's documented association with at least Jalapeno and Serrano peppers, these changes may be of significance, representing key adaptive changes among produce-specific Salmonella.…”
Section: Microbial Adaptation On Produce Commoditymentioning
confidence: 99%
“…Surprisingly, these changes have provided a substantial clue to potential areas of adaptation having occurred in genes responsible for propanediol utilization (pduF) and propanediol diffusion facilitator (pudB) genes. Interestingly, propanediol is a metabolite resulting from ripening or rotting of plant tissues (Bobik et al, 1997;Brandl et al, 2013;Goudeau et al, 2013). Previous studies revealed that populations of mutants deficient in propanediol utilization were several logs lower than wild-type strains grown in cilantro (Goudeau et al, 2013).…”
Section: Microbial Adaptation On Produce Commoditymentioning
confidence: 99%
“…To date their role has been tied to their participation in the detoxification of cytotoxic quinones produced as antibacterial compounds by many plants [1]. A transcriptome study in Salmonella typhimurium has shown >100-fold up-regulation of an azoreductases during growth in lesions on cilantro and lettuce leaves versus in vitro growth [10]. A second study also showed significant up-regulation of Escherichia coli azoreductase during infection of radishes [6].…”
Section: Introductionmentioning
confidence: 99%